Eksistensi Balian Usada Dalam Pengobatan Pada Masyarakat Desa Tiga, Kecamatan Susut, Bangli - Bagus Arya Putra, I Gusti; Suwena, I Wayan (Humanis; Vol 20 No 1 (2017), 2017)
The advancement of Western modern medication is not forever able to provide total remedy for the patient. Complement to the existing treatment, the community at Tiga Village, District of Susut, Bangli, is still seeking traditional treatment as an alternative of therapy. Whereas this research aims to find out: (a) why balian usada is still exist in health service, and (b) how is the process and mechanism of health treatment system performed by balian usada in treating the patient. The choice of therapy towards balian usada can be examined through the health ecology approach, the reason to choose balian usada as alternative of therapy can be examined through health belief model theory. The concept being used in this research is existence concept, balian usada concept, and treatment concept. Therefore, this research is using ethnography research method.The result of research shows that the existence of balian usada in health service at Tiga Village up to now is still high. It is influenced by four factors, namely (a) the factor of patients’ closeness to balian usada; (b) factor of the same cultural background; (c) factor of community’s trust towards balian usada; and (d) cost factor. Meanwhile the process and mechanism of health treatment system on treating patient applied by balian usada at Tiga Village, is starting from diagnosing the disease with various means. Related to the treatment and therapy for the patient, balian usada has a guideline on Lontar Usada and verbal knowledge hereditarily.